2021
DOI: 10.3390/ijerph18178936
|View full text |Cite
|
Sign up to set email alerts
|

Implementing Digital Trainings within Medical Rehabilitations: Improvement of Mental Health and Synergetic Outcomes with Healthcare Service

Abstract: The need for new technologies in healthcare services has been stressed. However, little is known about the effectiveness of digital interventions integrated in psychosomatic rehabilitation processes. Data from 724 patients from psychosomatic rehabilitation clinics were analyzed with regard to the effectiveness of digital trainings indicated by a change in symptoms related to depression, anxiety, stress, and loneliness from pre– to post–rehabilitation. Rehabilitation satisfaction was examined in association wit… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 47 publications
0
3
0
1
Order By: Relevance
“…In general, during periods of high infection rates or rising incidences, patients have avoided medical treatments [39]. Reasons include recommended movement restrictions, but also to avoid exposing themselves to the potential risk of infection.…”
Section: Communicationmentioning
confidence: 99%
“…In general, during periods of high infection rates or rising incidences, patients have avoided medical treatments [39]. Reasons include recommended movement restrictions, but also to avoid exposing themselves to the potential risk of infection.…”
Section: Communicationmentioning
confidence: 99%
“…Home schooling of children, short-time allowance and missing equipment for a smooth transition to remote work are only a few of the numerous problems employees had to face that are possible causes for increased stress regarding working environment and job security. Another study showed similar results concerning the impact of pre-rehabilitation scores on rehabilitation effectiveness during the pandemic [ 26 ]. They collected data from 1718 patients through an online survey between July 2020 and April 2021 using different questionnaires for the mental markers depression, anxiety, perceived stress and loneliness.…”
Section: Discussionmentioning
confidence: 58%
“…Rehabilitation goals were measured by an 8-item scale (consisting of the possible rehabilitation goals that patients aimed to achieve during the rehabilitation) that has shown acceptable reliability and validity [ 40 ]. Sample items included “Improvement of my flexibility and endurance.” Answers were rated on a 4-point Likert scale ranging from 1 (not at all) to 4 (completely).…”
Section: Methodsmentioning
confidence: 99%